Stabilisation and financial adjustment in the Caribbean : a retrospective - Jones-Hendrickson, S. B. (1999)
Discusses the issues of stabilisation and financial adjustment in a set-theoretic framework. Focuses on the critical moments of policy adjustments in the Caribbean, given the present era of internalisation, liberalisation and globalisation. Contends that the region was in many respects a reactive participant to stabilisation and of adjustment as opposed to an active participant.